2011
DOI: 10.3168/jds.2010-3742
|View full text |Cite
|
Sign up to set email alerts
|

β-Galactosidase activity of commercial lactase samples in raw and pasteurized milk at refrigerated temperatures

Abstract: Many consumers are unable to enjoy the benefits of milk due to lactose intolerance. Lactose-free milk is available but at about 2 times the cost of regular milk or greater, it may be difficult for consumers to afford. The high cost of lactose-free milk is due in part to the added cost of the lactose hydrolysis process. Hydrolysis at refrigerated temperatures, possibly in the bulk tank or package, could increase the flexibility of the process and potentially reduce the cost. A rapid β-galactosidase assay was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…Horner et al [19] evaluated the lactose hydrolysis of raw and pasteurized milk using four commercial Kluyveromyces    β -galactosidases at 2°C for 72 h. The authors observed that the fourfold increase in the enzyme concentration doubled the hydrolyzed lactose concentration in the milk after a 12 h reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Horner et al [19] evaluated the lactose hydrolysis of raw and pasteurized milk using four commercial Kluyveromyces    β -galactosidases at 2°C for 72 h. The authors observed that the fourfold increase in the enzyme concentration doubled the hydrolyzed lactose concentration in the milk after a 12 h reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the temperature of 8°C for milk storing was selected mainly in order to limit the growth of psy-chrotrophic microflora and to preserve the activity of lactase. The lactase of K. lactis source shows an increase in the activity of 85-95% at 38°C as compared to that measured at 4-5°C (Mlichová and Rosenberg, 2006; Horner et al ., 2011). In the cheese making process the increase of temperature during milk warming (35°C) and the cooking of curd (42°C), allow the complete hydrolysis of the residual lactose before the curd acidification drops pH below 5.5, limiting the activity of the lactase.…”
Section: Discussionmentioning
confidence: 99%
“…The high concentration of lactase needed was probably due to the specific operative conditions rather than the use of raw sheep’s milk. In cow’s milk, no differences have been observed in lactase activity in relation to the type of milk (raw or pasteurized) or in relation to milk fat content (Horner et al ., 2011). The only modification proposed in the manufacturing of lactose-free variants of Pecorino di Osilo , fresh ricotta and Ricotta mustia cheeses, was the replacement of raw sheep’s milk with the lactose-free sheep’s milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations